N.Karimov's viola transcriptions in the pedagogical repertoire (on the example of the transcription of «Kuy» by M.Sagatov) - Бекенова, Айжан (Pedagogy and Psychology, 2021)
In the Kazakh educational process today, in addition to the generally recognized arrangements and treatments of world music classics and original works for viola, national music adapted for viola is actively involved. There are several collections of works for viola edited, arranged and processed by such authors as A.Nurbayeva, E.Liberchuk, Ya.Fudimana, N.Sagimbayeva, D.Makhmud. The musical literature presented in these collections is widely used at different levels of education – by students of music schools, colleges and even universities of the republic, which is mainly due to the limited repertoire. The article deals with the transcription of N.Karimov's «Kuy» for violin and chamber orchestra by M. Sagatov as one of the first experiments in interpreting the sound of dombra kuy in viola music.